2010
DOI: 10.1086/656720
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cervical White Blood Cell Infiltrate Is Associated with Genital HIV Detection in a Longitudinal Cohort of Antiretroviral Therapy–Adherent Women

Abstract: Despite antiretroviral therapy adherence and clinically suppressed plasma viremia, HIV was intermittently detected in genital secretions and was associated with subclinical inflammation and cells trafficking to the cervical mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
(58 reference statements)
3
28
0
Order By: Relevance
“…We found that 39.5% of women with undetectable PVL had detectable HIV-DNA in the genital tract, a rate very similar to those previously reported (median 34%, IQR = 30–40) [8][10], [15]–[17]. Overall, there was a positive correlation between HIV-DNA shedding in the genital tract and the level of HIV-DNA in PBMCs, although this correlation was less pronounced than the one we previously found between gut-associated lymphoïd tissue and blood [18].…”
Section: Discussionsupporting
confidence: 90%
“…We found that 39.5% of women with undetectable PVL had detectable HIV-DNA in the genital tract, a rate very similar to those previously reported (median 34%, IQR = 30–40) [8][10], [15]–[17]. Overall, there was a positive correlation between HIV-DNA shedding in the genital tract and the level of HIV-DNA in PBMCs, although this correlation was less pronounced than the one we previously found between gut-associated lymphoïd tissue and blood [18].…”
Section: Discussionsupporting
confidence: 90%
“…2,31 Genital infections associated with significant inflammation, including gonorrhea, chlamydia, yeast, and herpes, have been associated with increased rates of genital HIV-1 RNA 32,33 and DNA 34 shedding while treatment of these infections has been associated with a decrease in the detection of HIV-1 in genital secretions. 35,36 In this study, the only infection significantly associated with increased HIV-1 RNA shedding was yeast vaginitis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, although PVL directly correlates with vaginal viral load (VVL), increases in vaginal shedding may occur independent of PVL. 29 One serodiscordant couples study found no transmission where the infected person had a PVL of 1500 copies/mL or less. 30 Other studies, however, have found that any shedding of HIV-1 RNA in the vaginal compartment has the potential to increase the risk of sexual 30,31 and perinatal transmission.…”
mentioning
confidence: 99%